Broken Minds and Shattered Bodies: Re-mapping the British Society in Hilary Mantel’s Every Day is Mother’s Day and Wolf Hall - PANDEY, DR SANJAY PRASAD; WANI, ABDUL WAHIED (The journal of contemporary issues in business and government, 2021)
Hilary Mantel, a well-established British novelist, needs no introduction as her fame rests not only on the basis of the volumes of works she has published but also on the basis of awards and honours she has received due to her prominent works. The present research paper seeks to explore some hidden aspects of the British society and the hollowness of the relationships. She has taken the themes how even the family members do not show the ultimate devotion, keenness and loyalty to one another. There is no comfort even in the royal court. She has depicted the Tudor dynasty in her novel Wolf Hall. This novel has won the Booker Prize in 2009 and after that its sequel Bring up the Bodies has also won the same prize in 2012. Mantel is known as a historical novelist and present paper encompasses such recurring themes and motifs in her select novels. In this paper two novels Every Day is Mother’s Day and Wolf Hall have been taken for analysis from the critical camera. The theories ‘Simulacra’ and ‘Hyperreality’ coined by Jean Baudrillard also have been applied on Hilary Mantel’snovels.